Systematic Literature Review: Transforming Learning Through Artificial Sintelligence (AI) and Challenges for Educators in Elementary School Learning - Septiani Juanda; Farida Farida; Ayu Reza Ningrum (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2026)
This study aims to analyze the transformation of artificial intelligence (AI)- based learning and identify the challenges of its implementation in elementary schools. The method used was a Systematic Literature Review (SLR) of 15 articles from relevant national and international journals. The results show that AI can transform learning to be more personalized, interactive, and adaptive, and increase learning effectiveness through automated feedback and student data analysis. Furthermore, the role of teachers shifts to that of facilitators and collaborators. However, AI implementation still faces various challenges, such as limited teacher competency, infrastructure, and ethical and privacy issues. Therefore, comprehensive preparedness is needed to ensure optimal and sustainable use of AI to support improvements in the quality of elementary education.